Combination of Metal Coordination Tetrahedra and Asymmetric Coordination Geometries of Sb(III) in the Organically Directed Chalcogenidometalates: Structural Diversity and Ion‐exchange Properties. Issue 2 (26th January 2016) - Feng, Mei‐Ling; Wang, Kai‐Yao; Huang, Xiao‐Ying
Abstract: Chalcogenidometalates exhibit rich and diverse structures and properties applicable to ion exchange, thermoelectrics, photocatalysis, nonlinear optics, and so on. This personal account summarizes our recent progress in constructing chalcogenidometalates by combining metal coordination tetrahedra and the asymmetric coordination geometries of Sb 3+ in the presence of organic species (typically organic amines and metal‐organic amine complexes), which has been demonstrated as an effective strategy for synthesizing chalcogenidometalates with diversified structures and interesting properties. The linkage modes of asymmetric SbQ n ( n = 3, 4) geometries and group 13 (or 14) metal coordination tetrahedra are analyzed, and the secondary building units (SBUs), with different compositions and architectures, are clarified. The crucial role and function of organic species in the formation of chalcogenidometalates are explored, with an emphasis on their powerful structure‐directing features. In particular, some chalcogenidometalates in this family exhibit excellent ion‐exchange properties for Cs + and/or Sr 2+ ions; the factors affecting ion‐exchange properties are discussed to understand the underlying ion‐exchange mechanism. Abstract : The synthetic strategy of the combination of metal tetrahedra and asymmetric coordination polyhedra of Sb(III) in the presence of various organic species under solvothermal conditions leads to new chalcogenidometalates with diverse structures and ion‐exchange properties.